Evaluación de las variables del desempeño cooperativo, con enfoque en el buen vivir en la provincia de Santo Domingo de los Tsáchilas - Domínguez Cedeño, Anderson Fidel (2016)
The objective of this research was to evaluate the variables of the cooperative performance focusing on the Good Living, Savings and credit cooperatives in the province of Santo Domingo of the Tsachilas. Three phases were structured methodological, the selection of variables, the implementation of the assessment tool and the improvement plan. The first phase through a bibliographic search was determined the variables of performance for cooperative based on the model of social balance of the International Cooperative Alliance. In the second phase was applied the evaluation tool to cooperatives being study, in addition surveys were applied to workers and partners to verify the information provided by the cooperative. With the variables that presented greater shortcomings was the proposal of a plan for improvement which consists of six actions with their respective deadlines, difficulty, impact, prioritization and responsible to enforce them. It was concluded that the savings and credit cooperatives in the province of Santo Domingo of the Tsachilas are complying with the cooperative performance in a 59%, the variables with the greatest shortcomings were between the cooperation and the contribution to the development of the community.